Pendidikan dan status ekonomi dengan kepatuhan perawatan gigi tiruan lepasan - Wiworo Haryani; Dwi Eni Purwati; S. Satrianingsih (Majalah Kedokteran Gigi Indonesia, 2017)
Education and economic status with removable denturescare users’ obedience. Indonesian usually less maintains dental and oral hygiene increasing 24% in prevalence edentulousness. In oral health, especially to avoid disturbances occurring due to loss of the tooth, it would require the replacement of missing teeth with artificial teeth. Removable denture care users’ obedience is supported by the level of education and economic status. The aim of this study is to determine the correlation between education and economic status with removable denture care wearers’ obedience. This research used observational analytic survey method with cross sectional design. The research location is in Puskesmas Pembantu Tompeyan, Tegalrejo, Yogyakarta working area. The population covers all residents who meet the inclusion criteria which are in the age of more than 20 years old, have their own income, have the will to be respondents, and can work together. The research time was on September until November 2016. The sampling technique is using saturated sampling technique and the sample’s number are 43. The research instrument is removable denture care users’obedience questionnaire in the form of 10 statement checklists.The results of the research were respondents with college education level have the greatest obedience was 13 people (30.2%), while respondents with middle economic status having the biggest obedience were 10 people (23.3%). According to Kendall's Tau test results, this research has a significant relationship between level of education and removable denture care users’ obedience of (p=0.049) and economic status andremovable denture care users’ obedience of (p=0.004). It can be concluded that there is a relationship between level of education and economic status with removable denture care users’ obedience. ABSTRAKDalam kesehatan gigi dan mulut terutama untuk menghindari gangguan-gangguan yang dapat terjadi akibat kehilangan gigi tersebut, maka diperlukan penggantian gigi yang hilang dengan gigi tiruan. Kepatuhan perawatan pemakai gigi tiruan lepasan didukung oleh tingkat pendidikan dan status ekonomi. Tujuan penelitian untuk mengetahui hubungan tingkat pendidikan dan status ekonomi dengan kepatuhan perawatan pemakai gigi tiruan lepasan. Metode penelitian ini menggunakan survei observasional dengan rancangan cross sectional. Lokasi penelitian di wilayah kerja Puskesmas Pembantu Tompeyan, Tegalrejo, Yogyakarta. Populasi meliputi seluruh warga yang memenuhi kriteria inklusi yaitu berusia lebih dari 20 tahun dan menggunakan protesa, sudah memiliki penghasilan, bersedia menjadi responden dan bisa bekerja sama. Waktu penelitian pada bulan September sampai dengan November 2016. Teknik pengambilan sampel dengan teknik total sampling dan jumlah sampel ada 43. Instrumen penelitian adalah kuesioner kepatuhan perawatan gigi tiruan berupa checklist 10 pernyataan. Hasil penelitian menunjukkan responden dengan tingkat pendidikan perguruan tinggi memiliki kepatuhan terbesar yaitu 13 orang (30,2%) sedangkan responden dengan status ekonomi sedang yang memiliki kepatuhan terbesar yaitu 10 orang (23,3%). Hasil uji Kendall’s Tau menunjukkan ada hubungan yang bermakna antara tingkat pendidikan dengan kepatuhan perawatan pemakai gigi tiruan lepasan (p=0,049) dan status ekonomi dengan kepatuhan perawatan pemakai gigi tiruan lepasan (p=0,004). Kesimpulan penelitian ini adalah ada hubungan antara tingkat pendidikan dan status ekonomi dengan kepatuhan perawatan pemakai gigi tiruan lepasan.